Weathering the Storm: How Mothers with Refugee Backgrounds Helped their Children with School During the COVID-19 Pandemic - Wilson-Forsberg, Stacey; Kimani-Dupuis, Rosemary; Masakure, Oliver (International Journal of Multicultural Education, 2024)
This paper focuses on the experiences of ten women in Canada with refugee backgrounds from the Horn of Africa as they helped their adolescent children (ages 12-18) navigate the challenges of at-home online learning during the global COVID-19 pandemic. We situate our analysis within specific aspects of Yosso’s (2005) Community Cultural Wealth framework to demonstrate that, while the women’s efforts were hampered by online learning technologies, they were able to harness aspirational and familial capital to keep their children engaged in schoolwork. The women felt deeply involved in their children’s education, particularly in terms of following up on children’s homework, monitoring their activities, and providing guidance.